Multi-blended learning model for remote area schools in pandemic Covid-19 situation - Bin Tahir, Saidna Zulfiqar; Mutmainnah; Mufidah , Nuril (Journal for Teaching and Education for Scholars, 2022)
The Covid-19 pandemic has swept across the world and affected all sectors. Likewise, this forces educators to innovate in supporting teaching and learning activities in education, especially in remote areas. Therefore, this study attempted to design a learning model based on a needs and situation analysis for schools located in remote regions of Maluku. This study employed the Research and Development (R&D) method using the 4D model (define, design, develop, and disseminate), which in this article only presents two stages, namely define and design. The research sample consisted of 170 subjects from five high schools in Buru Regency, Maluku. The data collected used a situational and needs analysis questionnaire, which was analyzed descriptively. The analysis results are used to design appropriate learning models for schools in remote areas. This study found that a learning model suitable for remote areas is a multi-blended learning model. This model is expected to contribute proportionally to the government and schools implementing learning in remote areas.